Integration of Merangin Local Wisdom in the Development of the E-Module of Basic Concepts of Elementary Biology - Shobrina Fitri; Nazurty Nazurty; Muhammad Sofwan (MASI Mandiri Edukasi, 2026)
Learning Basic Biology Concepts in the Primary School Teacher Education (PGSD) program is often delivered in a theoretical manner and remains insufficiently connected to students' ecological and cultural contexts. This study aimed to develop an e-module based on Merangin local wisdom, examine its feasibility and practicality, and analyze its potential as a contextual learning resource for elementary biology. The study applied a research and development design using the ADDIE framework, supported by qualitative exploration of local ecological knowledge. Data were collected through field observations, interviews with customary leaders and local environmental managers, analysis of curriculum documents, expert validation questionnaires, and student response questionnaires. The local wisdom integrated into the e-module comprised the Lubuk Larangan river conservation system, Rantau Kermas Customary Forest governance, and the Merangin Geopark, which were mapped onto ecosystem, environmental conservation, biodiversity, and evolution materials. Expert validation showed an overall feasibility score of 90.9%, categorized as highly feasible, while the limited practicality test with second-semester PGSD students produced a score of 89.4%, categorized as highly practical. These findings indicate that the e-module can bridge biological concepts with local ecological knowledge while strengthening cultural literacy and conservation awareness among pre-service elementary teachers.